2012
DOI: 10.1152/ajplung.00292.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Rho signaling by pathologic mechanical stretch is a “second hit” to Rho-independent lung injury induced by IL-6

Abstract: Birukova AA, Tian Y, Meliton A, Leff A, Wu T, Birukov KG. Stimulation of Rho signaling by pathologic mechanical stretch is a "second hit" to Rho-independent lung injury induced by IL-6. Am J Physiol Lung Cell Mol Physiol 302: L965-L975, 2012. First published February 17, 2012 doi:10.1152/ajplung.00292.2011.-Most patients with acute lung injury (ALI) and acute respiratory distress syndrome of septic and nonseptic nature require assisted ventilation with positive pressure, which at suboptimal range may further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 44 publications
(41 reference statements)
3
48
0
Order By: Relevance
“…Moreover, we found that the effects on the liver and kidney were only transient (Supplemental Figure 1, F-J). This model of pancreatitis-associated lung injury revealed activation of the signaling pathways IκB/NF-κB, p38, and RhoA (Supplemental Figure 2, A and B), which are known to be important for mediating damage in the lung (18,19).…”
Section: A Model For Sap-induced Lethal Alimentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, we found that the effects on the liver and kidney were only transient (Supplemental Figure 1, F-J). This model of pancreatitis-associated lung injury revealed activation of the signaling pathways IκB/NF-κB, p38, and RhoA (Supplemental Figure 2, A and B), which are known to be important for mediating damage in the lung (18,19).…”
Section: A Model For Sap-induced Lethal Alimentioning
confidence: 97%
“…Because IL-6R is only minimally expressed (mainly on hepatocytes and leukocytes), IL-6 trans-signaling dramatically increases the number of potential IL-6 target cells (16). The complexes involve the downstream kinase Jak-2 in order to phosphorylate the transcription factor STAT3 at Y705 (18,19). Tyrosine phosphorylation of Y705 is required for formation of homodimers and subsequent nuclear translocations.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the EC permeability response to IL-6 was not accompanied by significant changes in FA arrangement ( Figure 1C). Previous studies have shown more delayed EC permeability response to IL-6, which developed after 0.5-5.0 hours of stimulation (24) in contrast to more rapid (5-20 min) development of permeability caused by thrombin, which also was followed by recovery of EC barrier by 60 minutes after treatment (29). These time points were further used for analysis of thrombin-and IL-6-induced EC signaling and cytoskeletal remodeling.…”
Section: Ec Permeability Caused By Thrombin and Il-6 Is Associated Wimentioning
confidence: 99%
“…The signaling pathways activated in pulmonary endothelium by IL-6 are not clearly understood, and the precise mechanisms of IL-6-mediated EC barrier dysfunction remain to be elucidated. Our previous study suggests that IL-6-induced EC permeability is independent of RhoA signaling (24). In the current study, we used thrombin and IL-6 as model agents to investigate a role of vinculin in contractiledependent and contractile-independent mechanisms of EC barrier failure relevant to pathological conditions of lung vascular barrier dysfunction caused by circulating vasoactive agonists and proinflammatory cytokines.…”
mentioning
confidence: 98%
“…The pathologic role of Rho activation in animal models of acute lung injury and EC cultures stimulated with ALI-relevant agonists or high magnitude cyclic stretch is well recognized (29,39,40), and pharmacologic inhibition of the Rho pathway by prostanoids, simvastatin, S1P receptor agonist FTY720, or Rho kinase inhibitor Y-27632 has been proposed as a potential treatment of ALI (41)(42)(43)(44)(45). However, endogenous regulators of excessive Rho activation in ALI are not well characterized.…”
Section: Phosphorylation Of Sermentioning
confidence: 99%